SPATIAL ACCESSIBILITY OF HOSPITAL HEALTHCARE IN ŁÓDŹ VOIVODESHIP - Wiśniewski, Szymon (Quaestiones Geographicae, 2016)
The article seeks to analyse the accessibility of hospital healthcare to inhabitants of Łódź voivodeship in 2015. The analysis comprises all the communes of the Łódź region as well as those of the neighbouring voivodeships from which the theoretical time of reaching hospitals in Łódź voivodeship does not exceed the maximum time assumed in the research. Accessibility was determined in reference to 51 hospitals, assuming that their ‘attractiveness’ was related to the number of permanent beds they offered. The research was conducted using the three-step floating catchment area method (3SFCA).